Establishment of a Dual Real-Time PCR Assay for the Identification of African Swine Fever Virus Genotypes I and II in China - Gao, Qi; Feng, Yongzhi; Yang, Yunlong; Luo, Yizhuo; Gong, Ting; Wang, Heng; Gong, Lang; Zhang, Guihong; Zheng, Zezhong (Frontiers in Veterinary Science, 2022)
Since the first outbreak of ASFV genotype II in China in 2018, ASF has posed a significant threat to the swine industry. After the emergence of genotype I in China in 2020, the epidemic prevention and control have become more difficult. No effective commercial vaccine is currently available, and the disease is difficult to eradicate; therefore, the identification of the ASFV genotype is critical to establish biosafety control measures. In this study, a dual real-time PCR detection method based on B646L and E183L genes was developed to distinguish between ASFV genotypes I and II by specifically amplifying the genotype I E183L gene. The method is strongly specific, detects B646L and E183L genes simultaneously, and does not cross-react with PEDV, PCV, PRRSV, PRV, and CSFV. The double real-time PCR detection of ASFV genotypes I and II showed a B646L amplification curve, and only genotype I showed an E183L amplification curve, consistent with our expectations. The method has high sensitivity and the lowest copy numbers detected for recombinant plasmids B646L and E183L were 1.07 × 102 and 3.13 × 104 copies/μL, respectively. The method is reproducible, and the coefficient of variation for detecting the coefficient of variation (CV) values of the two recombinant plasmids was <2%. Seven samples were positive and 277 were negative, and the results of the two methods were consistent. The dual real-time PCR presented in this study provides a rapid detection method for the identification of ASFV genotypes I and II, which may lead to improving efficient prevention and control measures for ASF in China.